Melba's Gift Book of Australian Art and Literature. (London Melbourne : Hodder and Stoughton George Robertson & Co., 1915)
'Melba's Gift Book of Australian Art and Literature' produced about 1915 to raise money for the Belgian Relief Fund. It contains colour plate illustrations by well-known Australian artists including Norman Lindsay, George Lambert, Hans Heysen, Edward Phillips Fox, Ida Rentoul Outhwaite, Charles Nuttall and Arthur Streeton and also entries by various Australian writers including Ethel Turner, Henry Lawson, C.J. Dennis, Bernard O'Dowd, Mrs Aeneas Gunn and Louis Esson. There is also a colour reproduction of a portrait of Melba by Florence Rodway. Melba was an avid supporter and collector of Australian art and some of these artists were represented in her own private collection.(collections.museumsvictoria.com.au)
Online: https://collections.museumsvictoria.com.au/items/1775591
Boek
Keywords: Melba, Nellie; Wereldoorlog I; Australië; België